Pemanfaatan sekolah sebagai sarana pencegahan obesitas sejak dini pada remaja - Harry Freitag Luglio Muhammad (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2019)
Obesity among adolescents is a new nutritional problem in Indonesia. This is not only associated with increased risk for obesity in later life but also increased the risk for cardiovascular diseases, type 2 diabetes mellitus, hypertension, and other non-communicable diseases. Therefore an effective and integrated obesity prevention program is highly warranted. There are several community-based programs for obesity prevention that have been developed in the past few decades and school-based activity is one of the potential programs that could be implemented in the Indonesian setting. School is a strategic location for obesity prevention programs in the adolescents because school is the place where most of the adolescents spending their time outside their home. In addition, a school also a centralized community where health and nutrition promotion programs can be done at the same time. In 2012, the Indonesian Ministry of Health published a guidebook on the prevention and treatment of adolescents with obesity at school. However, this guideline only focusing on the role of health workers at puskesmas level and not detailing the role of the school in managing obesity prevention program. Thus, this review was made to provide an alternative solution for obesity prevention in adolescent via programs that can be done at school. Author aimed this review for school managers, puskesmas health workers, the local department of health, researcher and non-government organization that has the concern regarding adolescents health especially in relation to nutrition. This review can be a foundation for the development and implementation of school-based obesity prevention programs as well as a reference for the development of school policy.